1999
DOI: 10.1016/s0025-6196(11)65126-4
|View full text |Cite
|
Sign up to set email alerts
|

Prolactinoma Manifesting With Symptomatic Hydrocephalus

Abstract: Prolactinomas are the most common secretory adenomas of pituitary origin. They typically manifest with symptoms referable to their endocrinologic effects or, if of sufficient size, to visual changes due to compression of the optic chiasm. Pituitary adenomas manifesting with hydrocephalus are rare. To our knowledge, only three such P rolactin-producing tumors of the pituitary gland typically manifest with symptoms related to endocrine disturbances or, if large enough, to visual changes due to compression of vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 5 publications
1
9
0
1
Order By: Relevance
“…These findings tend to confirm previous observations in men that DA sensitivity is independent from age (25). Noteworthy, a good response has been documented, even in massive prolactinomas inducing hydrocephalus or a confusional state in this age group (16)(17)(18). A still unresolved issue is the need for systematic pharmacological treatment of hyperprolactinaemia in post-menopausal women.…”
Section: Medical Treatment Of Prolactinomasmentioning
confidence: 99%
“…These findings tend to confirm previous observations in men that DA sensitivity is independent from age (25). Noteworthy, a good response has been documented, even in massive prolactinomas inducing hydrocephalus or a confusional state in this age group (16)(17)(18). A still unresolved issue is the need for systematic pharmacological treatment of hyperprolactinaemia in post-menopausal women.…”
Section: Medical Treatment Of Prolactinomasmentioning
confidence: 99%
“…The false negative rate was 1 in 26 cases in the group treated with ISB, 2 in 23 cases in the colloid group, and 0% in the combined method group. This ratio was reported between 0.8% and 11% in various series (32,33,35,36,37,38). It was demonstrated that the false negative rate decreased with the increase in the experience of the surgeon.…”
Section: Discussionmentioning
confidence: 79%
“…As mentioned earlier, 9%-30% of metastases detected by re-examining the lymph nodes with serial sections could not be detected in routine pathologic infertility testing (10,41) This insufficiency could be removed by reducing the cross-sectional area from the lymph node and by cytokeratin immunohistochemical staining (i.e., specific monoclonal antibody) (41, 42). A learning curve (19,32) was reported in many related studies. An experienced surgeon who applied both methods together had an SLN detection rate of 94%, whereas this rate was 86% for newly recruited surgeons (43).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, macroadenomas are more frequent due to late diagnosis, especially in postmenopausal female and male patients, and these patients may present with mass effect and neuroophthalmic complaints (headache and visual field defect) (17). Rarely, cases of prolactinomas with hydrocephalus and trigeminal neuralgia have been reported (32).…”
Section: Clinical Features Of Hyperprolactinemic Patientsmentioning
confidence: 99%